PENGETAHUAN IBU DALAM MENERAPKAN GIZI SEIMBANG DENGAN STATUS GIZI PADA IBU HAMILDI PUSKESMAS KUTE SIANTAN TAHUN 2023 - Kaban, Ermawati Friska; Febrina, Trisya Yona; Margiyanti, Norma Jeepi (Ensiklopedia of Journal, 2023)
The nutrition of pregnant women needs attention because it greatly affects the development of the fetus they contain. The impact that arises from pregnant women who experience balanced nutrition deficiencies are exposure to Chronic Energy Deficiency (CED), Anemia and babies born prematurely and babies born with low weight (LBW). This study aims to determine the relationship between mother's knowledge in implementing balanced nutrition and nutritional status of pregnant women at the Kute Siantan Health Center in 2023 with a cross sectional design. The number of pregnant women in the study were 35 people with a total sampling. The results of the study showed that the mother's knowledge of implementing balanced nutrition was sufficient, namely 45.7%. The nutritional status of the mother is good nutrition 57.1%. The results of the chi-square statistical test showed that there was a relationship between mother's knowledge in implementing balanced nutrition and nutritional status of pregnant women at the Kute Siantan Health Center with a p-value of 002≤0.05. The conclusion of the study, the mother's nutritional status is adequate and the mother's knowledge is quite good. The research implications shown by the Kute Siantan Health Center are expected to empower cadres in providing information about balanced nutrition and monitoring the nutritional status of pregnant women by collaborating with family members, especially husbands, parents and siblings.